Pemberdayaan Masyarakat melalui Pengelolaan Terpadu Badan Usaha Milik Desa Bersama Sumberrejo Berkah Mandiri Sejahtera (SBMS) Lembaga Keuangan Desa (LKD) Kecamatan Sumberrejo Kabupaten Bojonegoro - Nabilah Amellia Putri; Yusuf Hariyoko; Indah Murti (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Community empowerment is one of the efforts to achieve community economic prosperity. Which is linked to issues of poverty and development. BUMDesma is a step from the government by collaborating with villages related to productive business and economy. The aim of this research is to identify Community Empowerment through the Management of BUMDesma Sumberrejo Berkah Mandiri Sejahtera (SBMS) Lkd Sumberrejo Bojonegoro District. The research method used is qualitative with descriptive methods. Based on the results and discussion using the ACTORS Theory by Sarah Cook and Steve Macualay, the resulting findings are that the authority is based on PDTT Ministerial Decree No.11 of 2021 and is already a legal entity. The formation of a business unit must be jointly approved through an Inter-Village Deliberation (MAD) as well as accountability for activities and financial management every 1 year. Capital participation from the village government and the private sector is very necessary to create new businesses apart from revolving funds (SPP) so optimal management is needed. BUMDesma is expected to achieve independence and create businesses where fifty-fifty is needed, meaning 50% of BUMDesma and 50% of the community. So there is a need for coordination and assistance or coaching.